THE RELATIONSHIP BETWEEN SELF-EFFICACY AND BLOOD GLUCOSE LEVELS AMONG DIABETES MELLITUS (DM) PATIENTS AT KEDURUS HEALTH CENTER, SURABAYA - Nilasari, Vandi Perdana; Zahroh, Chilyatiz; Ainiyah, Nur; Wardani, Erika Martining (Universitas Nahdlatul Ulama Surabaya, 2022)
Background: The decrease in Blood Glucose levels in patients with diabetes mellitus is influenced by self-efficacy. Objective: The purpose of this study was to determine the relationship between self-efficacy and blood glucose levels in patients with diabetes mellitus (DM) at Kedurus Health care Surabaya. Methods: The research design is correlational with cross-sectional. The population of this study to 75 people. With a sample of 63 respondents. Sampling technique with non-probability sampling technique purposive sampling type. The independent variable in this study is self-efficacy. The dependent variable is blood glucose levels in patients with diabetes mellitus type 2 at Kedurus Health Center Surabaya. The research instrument is a questionnaire. Data analysis with spearman Rho statistic test. Result: Based on the spearman rank obtained the level of significance ρ = 0,000 < a = 0,05 which means there is a relationship between self-efficacy and blood glucose levels in patients with diabetes mellitus (DM) at Kedurus health care Surabaya. Conclusion: Self-efficacy will give a good influence, especially on reducing blood glucose levels in patients with Diabetes Mellitus (DM). it is hoped that the support from nurses and good self-efficacy will have an impact on reducing blood glucose and preventing complications in patients with diabetes mellitus.